Maternal Leishmania infantum infection status has significant impact on leishmaniasis in offspring. - Angela J Toepp; Carolyne Bennett; Benjamin Scott; Reid Senesac; Jacob J Oleson; Christine A Petersen (Public Library of Science (PLoS), 2019)
Visceral Leishmaniasis is a deadly disease caused by Leishmania infantum, endemic in more than 98 countries across the globe. Although the most common means of transmission is via a sand fly vector, there is growing evidence that vertical transmission may be critical for maintaining L. infantum infection within the reservoir, canine, population. Vertical transmission is also an important cause of infant morbidity and mortality particularly in sub-Saharan Africa. While vertical transmission of visceralizing species of Leishmania has been reported around the globe, risk factors associated with this unique means of Leishmania transmission have not been identified therefore interventions regarding this means of transmission have been virtually non-existent. Furthermore, the basic reproductive number, (R0), or number of new L. infantum infections that one infected mother or dam can cause has not been established for vertical transmission, also hampering the ability to assess the impact of this means of transmission within reservoir of human hosts. Canine Leishmaniosis (CanL) is enzootic within a U.S. hunting dog population. CanL is transmitted within this population via transplacental transmission with no reported vector transmission, despite many repeated attempts to find infected sand flies associated with these dogs and kennels. This population with predominantly, if not solely, vertical transmission of L. infantum was used to evaluate the critical risk factors for vertical transmission of Leishmania and establish the R0 of vertical L. infantum infection. Evaluation of 124 animals born to eighteen dams diagnostically positive for infection with L. infantum showed that there was a 13.84x greater chance of being positive for L. infantum within their lifetime if the mother was also positive within her lifetime (RR: 13.84, 95% CI: 3.54-54.20, p-value: <0.0001). The basic reproductive number for vertically transmitted L. infantum within this cohort was 4.12. These results underscore that there is a high risk of L. infantum infection to transmit from mother to offspring. Targeted public health interventions and control efforts that address vertical transmission of L. infantum are necessary in endemic countries to eliminate visceral leishmaniasis.